Meningkatkan Niat Pembelian Hijau: Peran dari Kesadaran Nilai Hijau, Citra Merk Hijau, Kesadaran Risiko Hijau, dan Kepercayaan Hijau Penelitian Empiris pada Konsumen The Body Shop di Kota Yogyakarta - , RESHA FRIDIANTI; , Sudiyanti, S.E., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research proposes five novel constructs, green perceived value, green brand image, green perceived risk, green trust, and green purchase intentions and explore the positive relationship between green purchase intentions and its three drivers, green perceived value, green brand image, and green trust, and the negative relationship between green purchase intentions and its only driver, green perceived risk. The object of this research is customer of The Body Shop in Kota Yogyakarta. This research employs an empirical study by means of the questionnaire survey method to verify the hypotheses and to explore its managerial implications. The empirical results show that green perceived value, green brand image, and green trust are positively significant related to green purchase intentions, while green perceived risk is not negatively significant related to green purchase intentions. Furthermore, this study demonstrates that the relationship between green purchase intentions and their three antecedents â green perceived value, green brand image, and green perceived risk â are partially mediated by green trust. Hence, investing resources to increase green perceived value and green brand image is helpful to enhance green trust and green purchase intentions.